2019
DOI: 10.2134/jeq2018.10.0357
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation in Soil Nitrous Oxide Emissions from a Rehabilitated and Undisturbed Riparian Forest

Abstract: Riparian zones enhance water quality and provide wildlife habitat, but high nutrient input in agricultural landscapes causes nitrous oxide (N2O) emissions, potentially negating their benefits of C sequestration. The objectives of this study were to quantify spatiotemporal N2O emissions in a rehabilitated and undisturbed natural riparian forest. We also determined soil and vegetation characteristics, and their role in driving spatiotemporal N2O emissions. Mean N2O‐N emissions were not significantly (p < 0.05) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…Despite the large N 2 O emissions in the no-buffer control, they were not significantly different to the vegetated riparian buffers and the upslope maize. The findings were similar to Baskerville et al (2021) andDe Carlo et al (2019), who observed no significant differences in N 2 O emissions amongst the riparian zones. Baskerville et al, (2021) also reported that there were no significant differences when comparing these zones to the agricultural land.…”
Section: Gas Emissions In Upslope Maize and Downslope Riparian Buffer...supporting
confidence: 91%
“…Despite the large N 2 O emissions in the no-buffer control, they were not significantly different to the vegetated riparian buffers and the upslope maize. The findings were similar to Baskerville et al (2021) andDe Carlo et al (2019), who observed no significant differences in N 2 O emissions amongst the riparian zones. Baskerville et al, (2021) also reported that there were no significant differences when comparing these zones to the agricultural land.…”
Section: Gas Emissions In Upslope Maize and Downslope Riparian Buffer...supporting
confidence: 91%
“…Beneficial impacts of the RBS on both local terrestrial and aquatic environments were observed since rehabilitation was initiated, e.g., reduced soil respiration, enhanced wildlife habitat and maintenance of stream water temperature (Oelbermann et al, 2008). Concerning greenhouse gases, De Carlo et al (2019) found no significant differences in N 2 O emissions between the rehabilitated and an upstream natural riparian forests, which was confirmed later by Baskerville et al (2021), who also found lower N 2 O emissions in the RBS compared to an agricultural field adjacent to the rehabilitated RBS. Moreover, Mafa-Attoye et al (2020) detected significant differences in N-cycling bacterial communities between RBS and agricultural soils.…”
Section: Introductionmentioning
confidence: 63%
“…Remarkably high net average N 2 O uxes from soil have been measured in riparian forests 22 , and most of the studies were conducted in riparian alder stands [23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%